Diaphragm myoclonus followed by generalised atonia in a patient with trisomy 4p: unusual semiology in an unusual condition. Issue 4 (25th January 2016) - Varley, James; Wehner, Tim; Sisodiya, Sanjay
Abstract: In this report, we describe a female patient with trisomy 4p, a rare genetic condition, with unusual seizure semiology. The patient is one of the oldest reported survivors with this condition. This semiology was noted while she was being monitored by inpatient video telemetry. We observed a series of myoclonic shoulder jerks, followed by hiccup‐like episodes, and finally an atonic head drop. Corresponding ictal EEG showed semi‐rhythmic high‐amplitude slow waves with spikes superimposed over the frontotemporal areas. This semiology was confirmed as habitual by her parents. Subsequent hiccup‐like episodes had no EEG correlate, and the head drop was again associated with semi‐rhythmic high‐amplitude slow waves and superimposed spikes, more prominent over the right hemisphere. In addition, we review the several cases in which hiccups have been associated with seizures and how this may relate to the neural pathways involved in the pathophysiology of hiccups. We believe the ictal hiccup‐like episodes followed by atonia to be a seizure semiology that has not previously been documented. [ Published with video sequence ]